Peranan Perempuan Dalam Peningkatan Pendapatan Rumah Tangga Nelayan Di Desa Maitara - Nuraini A Damsiki (Jurnal Ilmiah Wahana Pendidikan, 2018)
Especially fishing easy to gain risks and have fluctuating income pattern. These have encouraged women, both housewives and daughters to get involved in increasing the familys income. The research method was a case study. In Maitara, there were 56 fishermans families whose wives worked in fisheries and 3 families in other economic activities. Sampling used a propotional stratified random sampling technique, in which data were collected through direct observations, interview and documentation study. Results showed that fishermens family communities in Maitara. The husband spent more time for productive activities as pure seine workers. The role of women was double, both in the productive activities, such as children care, cooking and washing. The role of women in the family to raise the income level was dependent upon the type of work done and the size of capital, but so far the income obtained by housewives could support the familys economic. Domestic activities couid also reduce living cost, since these could be done by themselves and assisted by their children.